Wear-resistant and stain-resistant UV coating and preparation method thereof

By adding modified anti-wear fillers to UV coatings and using a combination modification technology of fluorinated modifier and silane coupling agent, the shortcomings of UV coatings in terms of wear resistance and pollution resistance are solved, and the coating is achieved with high wear resistance and stain resistance.

CN119684887AActive Publication Date: 2025-03-25NANXIONG YALTON CHEM CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411788866.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-25
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Existing UV coatings have shortcomings in their wear and pollution resistance performance, especially in industrial equipment, outdoor buildings and scenarios where high-strength cleaning needs are needed.

Method used

By adding independently developed modified anti-wear filler to UV coatings, the filler is amine ester exchanged from methyl trifluoroacetate and diethylene triamine to make a fluorine structure-capped amide compound, i.e., a fluorinated modifier. Using corundum powder as a carrier, the chelating properties of the multivariate nitrogen structure in the fluorinated modifier molecule are loaded to the surface of corundum powder particles to promote coupling of silane coupling agent KH-570 on the corundum powder and grafting methacryloyloxy modification to the surface of corundum powder.

Benefits of technology

The modified anti-wear filler introduces fluoride with double-splitting fluoride into the coating, which improves the stain resistance and adhesion of the coating, enhances the wear resistance and protective properties of the coating, makes the coating not easy to fall off during friction and wear, and the deformation ability of the coating is improved to prevent cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a wear-resistant and stain-resistant UV coating and a preparation method thereof, and belongs to the technical field of UV coatings. The UV coating is prepared from the following components in parts by weight: 100 parts of acrylate resin, 18 to 26 parts of modified anti-wear filler, 20 to 25 parts of reactive diluent, 3 to 3.5 parts of photoinitiator, 5 to 7 parts of color paste, 0.8 to 1 part of matrix wetting agent, 1 to 1.2 parts of flatting agent and 0.5 to 0.7 part of defoaming agent, the modified anti-wear filler is prepared by the following steps: carrying out amine-ester exchange on methyl trifluoroacetate and diethylenetriamine to prepare a fluorine structure-terminated amide compound, namely a fluorinated modifier, and loading the alundum powder as a carrier to the surface of the alundum powder by using the chelating property of a multi-nitrogen structure in molecules of the fluorinated modifier, so as to prepare the modified anti-wear filler. Organic amine in the structure provides an alkaline environment on the surface of emery powder, in-situ promotes coupling of a silane coupling agent KH-570 in the emery powder, and compound modification is conducted on the surface of the emery powder; the introduction of the modified anti-wear filler endows the coating with good wear resistance and pollution resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a wear-resistant and anti-fouling UV coating and a preparation method thereof. Background Art

[0002] As an indispensable material in the industrial and civil fields, coatings play a key role in many industries. Especially in the construction, transportation, automobile and electronics industries, their excellent protective performance and decorative functions make them an indispensable material; among them, UV coatings have attracted widespread attention due to their low curing temperature, low volatility and fast curing speed.

[0003] However, existing UV coatings are insufficient in terms of wear resistance and resistance to pollutants, especially in industrial equipment, outdoor buildings, and scenarios requiring high-intensity cleaning requirements, and are difficult to meet. Summary of the invention

[0004] In order to solve the technical problems mentioned in the background technology, the purpose of the present invention is to provide a wear-resistant and anti-fouling UV coating and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A wear-resistant and anti-fouling UV coating comprises, by weight, 100 parts of acrylate resin, 18-26 parts of modified wear-resistant filler, 20-25 parts of active diluent, 3-3.5 parts of photoinitiator, 5-7 parts of color paste, 0.8-1 part of base wetting agent, 1-1.2 parts of leveling agent and 0.5-0.7 parts of defoaming agent.

[0006] The modified anti-wear filler is prepared by the following method: Step A1: premix diethylenetriamine, methyl trifluoroacetate and anhydrous tetrahydrofuran, preheat to 35-40°C, apply stirring at 60-90 rpm, slowly add triethylamine and react for 4-5 hours, then increase the pressure to 5-8 bar with nitrogen, continue to heat to 75-90°C and reflux for 2.5-4 hours, and remove tetrahydrofuran by rotary evaporation after the reaction to obtain a fluorinated modifier; Furthermore, the feed ratio of diethylenetriamine, methyl trifluoroacetate, triethylamine and anhydrous tetrahydrofuran is 0.1 mol: 0.22-0.25 mol: 8-14 mL: 50-70 mL, and triethylamine is used as an alkaline catalyst to promote amine ester exchange between methyl trifluoroacetate and diethylenetriamine.

[0007] Step A2: Mix the silane coupling agent KH-570 and the acidic ethanol aqueous solution, apply stirring at 120-150 rpm for hydrolysis at room temperature for 30-50 minutes to obtain a hydrolyzate, premix the corundum powder, the fluorinated modifier and acetone and heat to 40-50° C., add the hydrolyzate to ultrasonically disperse, let stand for 24 hours, take the bottom precipitate, wash with water, and dry to obtain a modified anti-wear filler; Furthermore, the feed ratio of corundum powder, fluorination modifier, silane coupling agent KH-570, acidic ethanol aqueous solution and acetone is 50g: 0.9-1.3g: 1.5-2g: 30-40mL: 60-80mL, the poly-nitrogen structure in the fluorination modifier molecule has a chelating effect and is preferentially loaded onto the surface of the corundum powder particles, the silane coupling agent KH-570 is hydrolyzed into silanol in an acidic alcohol water environment, and the organic amine in the fluorination modifier provides an alkaline environment on the surface of the corundum powder, promotes the coupling of silanol and corundum powder in situ, and grafts methacryloyloxy modification onto the surface of the corundum powder.

[0008] Preferably, the pH value of the acidic ethanol solution is 2-3, and the volume fraction of ethanol is 40-55%. The conditional silane coupling agent KH-570 is easy to fully hydrolyze and maintain a stable hydrolysis state, and is easy to be loaded on the surface of the corundum powder in situ.

[0009] Preferably, the fineness of the corundum powder is 600-1000 mesh, which is easy to disperse, ensuring the fineness of the coating while providing good loadability.

[0010] Preferably, the acrylate resin is selected from polyurethane acrylate resin, which has good bonding properties with most substrates, good wear resistance and weather resistance, and high applicability.

[0011] Preferably, the active diluent is compounded from dipropylene glycol diacrylate and trimethylolpropane triacrylate to ensure a good thinning effect while obtaining a good degree of crosslinking and maintaining excellent toughness of the coating.

[0012] A method for preparing a wear-resistant and anti-fouling UV coating comprises the following steps: mixing and diluting an acrylate resin and an active diluent, adding a color paste, a base wetting agent, a leveling agent and a defoaming agent, and finally adding a modified anti-wear filler and a photoinitiator for grinding and dispersion to obtain a UV coating.

[0013] Beneficial effects of the present invention: The invention adds a modified anti-wear filler independently developed in the existing UV coating system to give the coating good wear resistance and anti-fouling properties. The modified anti-wear filler is prepared by amine ester exchange of methyl trifluoroacetate and diethylenetriamine to prepare an amide compound with a fluorine structure end-capping, namely a fluorinated modifier. Then, corundum powder is used as a carrier, and the chelating property of the polynary nitrogen structure in the fluorinated modifier molecule is used to load it on the surface of the corundum powder particles. The organic amine in the structure provides an alkaline environment on the surface of the corundum powder, promotes the in-situ coupling of the silane coupling agent KH-570 on the corundum powder, and performs composite modification on the surface of the corundum powder. Compared with the existing compound coating, the invention has the following advantages: 1. In the coating composite system, the fluorinated modifier introduces amphiphilic fluoride into the coating. With corundum powder as the carrier, it is not easy to segregate in the coating, giving the coating uniform anti-fouling properties, and has little effect on the adhesion and mechanical properties of the coating; 2. In the coating curing coating, the surface of the corundum powder is grafted with methacryloyloxy by silane coupling agent KH-570, which is co-crosslinked with the acrylate resin under light curing, greatly improving the bonding strength between the corundum powder and the resin, making it difficult to fall off during friction and wear, thereby giving full play to the wear-resistant effect; The fluorinated modifier is filled in the cross-linked layer of corundum powder and resin. Its fluorine structure can reduce the interfacial tension of the resin, so that the stress generated by shrinkage during the cross-linking process is released. In addition, the fluorine structure can increase the mobility of the polymer chain, so that the coating can be better deformed and less likely to crack when subjected to external force, making the protective performance of the coating more stable. DETAILED DESCRIPTION

[0014] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0015] Example 1, preparation of wear-resistant and anti-fouling UV coating, the specific implementation process is as follows: (1) Preparation of modified anti-wear filler Step A1: pre-mix diethylenetriamine, methyl trifluoroacetate and anhydrous tetrahydrofuran, pre-heat to 35°C, stir at 60rpm, slowly add triethylamine and react for 5h, then pressurize with nitrogen to 5bar, continue to heat to 75°C and reflux for 4h, wherein the feed ratio of diethylenetriamine, methyl trifluoroacetate, triethylamine and anhydrous tetrahydrofuran is 0.1mol:0.22mol:8mL:50mL, and after the reaction, remove tetrahydrofuran by rotary evaporation to obtain a fluorinated modifier.

[0016] Step A2: prepare a 40% mass fraction ethanol aqueous solution and adjust the pH value to 3 with formic acid, mix the silane coupling agent KH-570 and the acidic ethanol aqueous solution, apply stirring at 120 rpm for hydrolysis at room temperature for 30 minutes to obtain a hydrolyzate, premix the corundum powder, the fluorination modifier and acetone and heat them to 40°C, add the hydrolyzate for ultrasonic dispersion, wherein the feed ratio of corundum powder, fluorination modifier, silane coupling agent KH-570, acidic ethanol aqueous solution and acetone is 50g:1.3g:1.5g:30mL:80mL, the corundum powder is selected from 600 mesh micropowder, and after standing for 24 hours, the bottom precipitate is washed with water and dried to obtain a modified anti-wear filler.

[0017] (2) Preparation of UV coating The raw materials are taken according to weight parts, 100 parts of acrylate resin, U-Cure 9303 type polyurethane acrylate resin is used in the implementation process; 18 parts of modified anti-wear filler, which is self-made in this embodiment; 20 parts of active diluent, dipropylene glycol diacrylate and trimethylolpropane triacrylate are compounded in a mass ratio of 2:1 in the implementation process; 3 parts of photoinitiator, photoinitiator 1173 is used in the implementation process; 5 parts of color paste, commercially available oily black paste is used in the implementation process; 0.8 parts of base wetting agent, HY-6086 type raw material is used in the implementation process; 1 part of leveling agent, HY-6410 type raw material is used in the implementation process; 0.5 parts of defoaming agent, HY-1040F type raw material is used in the implementation process.

[0018] Add the acrylic resin and active diluent into a mixer, stir at a low speed of 30 rpm to dilute, then add the color paste, base wetting agent, leveling agent and defoaming agent and mix evenly, finally add the modified anti-wear filler and photoinitiator and grind and disperse to obtain a UV coating.

[0019] Example 2, preparation of wear-resistant and anti-fouling UV coating, the specific implementation process is as follows: (1) Preparation of modified anti-wear filler Step A1: pre-mix diethylenetriamine, methyl trifluoroacetate and anhydrous tetrahydrofuran, pre-heat to 40°C, stir at 90rpm, slowly add triethylamine and react for 4h, then pressurize to 8bar with nitrogen, continue to heat to 90°C and reflux for 2.5h, wherein the feed ratio of diethylenetriamine, methyl trifluoroacetate, triethylamine and anhydrous tetrahydrofuran is 0.1mol:0.25mol:14mL:70mL, and after the reaction, remove tetrahydrofuran by rotary evaporation to obtain a fluorinated modifier.

[0020] Step A2: prepare an ethanol aqueous solution with a mass fraction of 55% and adjust the pH value to 2 with formic acid, mix the silane coupling agent KH-570 and the acidic ethanol aqueous solution, apply stirring at 150 rpm for hydrolysis at room temperature for 50 minutes to obtain a hydrolyzate, premix the corundum powder, the fluorination modifier and acetone and heat them to 50°C, add the hydrolyzate for ultrasonic dispersion, wherein the feed ratio of corundum powder, fluorination modifier, silane coupling agent KH-570, acidic ethanol aqueous solution and acetone is 50g:0.9g:2g:40mL:60mL, the corundum powder is selected from 1000 mesh micropowder, and after standing for 24 hours, the bottom precipitate is washed with water and dried to obtain a modified anti-wear filler.

[0021] (2) Preparation of UV coating The raw materials are taken according to weight parts, 100 parts of acrylate resin, U-Cure 9303 type polyurethane acrylate resin is used in the implementation process; 26 parts of modified anti-wear filler, which is self-made in this embodiment; 25 parts of active diluent, dipropylene glycol diacrylate and trimethylolpropane triacrylate are compounded in a mass ratio of 2:1 in the implementation process; 3.5 parts of photoinitiator, photoinitiator 1173 is used in the implementation process; 7 parts of color paste, commercially available oily black paste is used in the implementation process; 1 part of base wetting agent, HY-6086 type raw material is used in the implementation process; 1.2 parts of leveling agent, HY-6410 type raw material is used in the implementation process; 0.7 parts of defoaming agent, HY-1040F type raw material is used in the implementation process.

[0022] Add the acrylic resin and active diluent into a mixer, stir at a low speed of 30 rpm to dilute, then add the color paste, base wetting agent, leveling agent and defoaming agent and mix evenly, finally add the modified anti-wear filler and photoinitiator and grind and disperse to obtain a UV coating.

[0023] Example 3, preparation of wear-resistant and anti-fouling UV coating, the specific implementation process is as follows: (1) Preparation of modified anti-wear filler Step A1: pre-mix diethylenetriamine, methyl trifluoroacetate and anhydrous tetrahydrofuran, pre-heat to 35°C, stir at 60rpm, slowly add triethylamine and react for 5h, then pressurize with nitrogen to 6bar, continue to heat to 80°C and reflux for 3h, wherein the feed ratio of diethylenetriamine, methyl trifluoroacetate, triethylamine and anhydrous tetrahydrofuran is 0.1mol:0.23mol:10mL:60mL, and after the reaction, remove tetrahydrofuran by rotary evaporation to obtain a fluorinated modifier.

[0024] Step A2: prepare a 50% mass fraction ethanol aqueous solution and adjust the pH value to 3 with formic acid, mix the silane coupling agent KH-570 and the acidic ethanol aqueous solution, apply stirring at 150 rpm for hydrolysis at room temperature for 40 minutes to obtain a hydrolyzate, premix the corundum powder, the fluorination modifier and acetone and heat them to 45°C, add the hydrolyzate for ultrasonic dispersion, wherein the feed ratio of corundum powder, fluorination modifier, silane coupling agent KH-570, acidic ethanol aqueous solution and acetone is 50g:1.1g:1.7g:35mL:70mL, the corundum powder is selected from 800 mesh micropowder, and after standing for 24 hours, the bottom precipitate is washed with water and dried to obtain a modified anti-wear filler.

[0025] (2) Preparation of UV coating The raw materials are taken according to weight parts, 100 parts of acrylate resin, U-Cure 9303 type polyurethane acrylate resin is used in the implementation process; 20 parts of modified anti-wear filler, which is self-made in this embodiment; 22 parts of active diluent, dipropylene glycol diacrylate and trimethylolpropane triacrylate are compounded in a mass ratio of 2:1 in the implementation process; 3.2 parts of photoinitiator, photoinitiator 1173 is used in the implementation process; 6 parts of color paste, commercially available oily black paste is used in the implementation process; 0.9 parts of base wetting agent, HY-6086 type raw material is used in the implementation process; 1.1 parts of leveling agent, HY-6410 type raw material is used in the implementation process; 0.6 parts of defoaming agent, HY-1040F type raw material is used in the implementation process.

[0026] Add the acrylic resin and active diluent into a mixer, stir at a low speed of 30 rpm to dilute, then add the color paste, base wetting agent, leveling agent and defoaming agent and mix evenly, finally add the modified anti-wear filler and photoinitiator and grind and disperse to obtain a UV coating.

[0027] Example 4, preparation of wear-resistant and anti-fouling UV coating, the specific implementation process is as follows: (1) Preparation of modified anti-wear filler Step A1: pre-mix diethylenetriamine, methyl trifluoroacetate and anhydrous tetrahydrofuran, pre-heat to 40°C, stir at 90rpm, slowly add triethylamine and react for 5h, then pressurize with nitrogen to 7bar, continue to heat to 85°C and reflux for 3h, wherein the feed ratio of diethylenetriamine, methyl trifluoroacetate, triethylamine and anhydrous tetrahydrofuran is 0.1mol:0.22mol:12mL:70mL, and after the reaction, remove tetrahydrofuran by rotary evaporation to obtain a fluorinated modifier.

[0028] Step A2: prepare a 45% mass fraction ethanol aqueous solution and adjust the pH value to 2 with formic acid, mix the silane coupling agent KH-570 and the acidic ethanol aqueous solution, apply stirring at 150 rpm for hydrolysis at room temperature for 40 minutes to obtain a hydrolyzate, premix the corundum powder, the fluorination modifier and acetone and heat them to 45°C, add the hydrolyzate for ultrasonic dispersion, wherein the feed ratio of corundum powder, fluorination modifier, silane coupling agent KH-570, acidic ethanol aqueous solution and acetone is 50g:1.2g:1.6g:40mL:70mL, the corundum powder is selected from 800 mesh micropowder, and after standing for 24 hours, the bottom precipitate is washed with water and dried to obtain a modified anti-wear filler.

[0029] (2) Preparation of UV coating The raw materials are taken according to weight parts, 100 parts of acrylate resin, U-Cure 9303 type polyurethane acrylate resin is used in the implementation process; 22 parts of modified anti-wear filler, which is self-made in this embodiment; 23 parts of active diluent, dipropylene glycol diacrylate and trimethylolpropane triacrylate are compounded in a mass ratio of 2:1 in the implementation process; 3.2 parts of photoinitiator, photoinitiator 1173 is used in the implementation process; 6 parts of color paste, commercially available oily black paste is used in the implementation process; 0.9 parts of base wetting agent, HY-6086 type raw material is used in the implementation process; 1 part of leveling agent, HY-6410 type raw material is used in the implementation process; 0.5 parts of defoaming agent, HY-1040F type raw material is used in the implementation process.

[0030] Add the acrylic resin and active diluent into a mixer, stir at a low speed of 30 rpm to dilute, then add the color paste, base wetting agent, leveling agent and defoaming agent and mix evenly, finally add the modified anti-wear filler and photoinitiator and grind and disperse to obtain a UV coating.

[0031] Comparative Example 1, referring to Example 4, the modified anti-wear filler is replaced with the same weight portion of KH-570 coupled corundum powder, and the rest of the implementation process is exactly the same, wherein the preparation method of KH-570 coupled corundum powder is: mixing the silane coupling agent KH-570 and the ethanol aqueous solution, adjusting the pH value to 3.5 with formic acid, stirring and hydrolyzing at room temperature for 1 hour, then adding 800 mesh corundum powder for ultrasonic dispersion, standing for 24 hours, taking the bottom precipitate, washing and drying. During the implementation process, the feed ratio of corundum powder, silane coupling agent KH-570 and ethanol aqueous solution is 50g:2.5g:100mL, and the volume fraction of ethanol aqueous solution is 50%.

[0032] Comparative Example 2: This comparative example is based on Comparative Example 1, except that 0.4 parts of 2-perfluorooctyl ethyl acrylate is further added to the raw material formula, and KH-570 coupled corundum powder is added together, and the rest of the implementation process is exactly the same.

[0033] Take the ceramic treated low carbon steel sheet as the substrate, apply the UV coating prepared above to the substrate surface with an applicator, and apply 220W / m 2 The coating was cured by ultraviolet radiation of high intensity for 5 minutes and then left to stand for 24 hours. The coating properties were tested as follows: The cured thickness of the coating was tested in accordance with GB / T 13452.2-2008; the adhesion of the coating was tested in accordance with GB / T 9286-2021; the wear resistance of the coating was tested in accordance with GB / T 1768-2006, with a rotation speed of 60 rpm, a load of 1000 g, and a running number of 500 times; the T-bend test was performed in accordance with GB / T 30791-2014; the surface water contact angle of the coating was tested in accordance with ASTM D7490-13; the specific test results are shown in Table 1: Table 1

[0034] It can be seen from the test results in Table 1 that the coating prepared in the embodiment has excellent wear resistance after curing, the T-bend test reaches 0T, the coating has excellent toughness, is not easy to crack and fall off during deformation, and has a high water contact angle and good anti-fouling performance.

[0035] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0036] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A wear-resistant and anti-fouling UV coating, characterized in that: The composition comprises, by weight: 100 parts of acrylate resin, 18-26 parts of modified anti-wear filler, 20-25 parts of active diluent, 3-3.5 parts of photoinitiator, 5-7 parts of color paste, 0.8-1 parts of matrix wetting agent, 1-1.2 parts of leveling agent and 0.5-0.7 parts of defoaming agent; The modified anti-wear filler is prepared by the following method: Step A1: premix diethylenetriamine, methyl trifluoroacetate and anhydrous tetrahydrofuran, preheat to 35-40°C, stir and slowly add triethylamine to react for 4-5h, then pressurize with nitrogen to 5-8bar, continue to heat to 75-90°C and reflux for 2.5-4h, after the reaction is completed, remove tetrahydrofuran by rotary evaporation to obtain a fluorinated modifier; Step A2: Mix the silane coupling agent KH-570 and the acidic ethanol aqueous solution, stir and hydrolyze at room temperature for 30-50 minutes to obtain a hydrolyzate, premix the corundum powder, the fluorinated modifier and acetone and heat to 40-50°C, add the hydrolyzate to ultrasonically disperse, let stand for 24 hours, take the bottom precipitate, wash with water, and dry to obtain a modified anti-wear filler.

2. The wear-resistant and anti-fouling UV coating according to claim 1, characterized in that: The feed ratio of diethylenetriamine, methyl trifluoroacetate, triethylamine and anhydrous tetrahydrofuran is 0.1 mol: 0.22-0.25 mol: 8-14 mL: 50-70 mL.

3. The wear-resistant and anti-fouling UV coating according to claim 2, characterized in that: The feed ratio of corundum powder, fluorination modifier, silane coupling agent KH-570, acidic ethanol aqueous solution and acetone is 50g: 0.9-1.3g: 1.5-2g: 30-40mL: 60-80mL.

4. The wear-resistant and anti-fouling UV coating according to claim 3, characterized in that: The pH value of the acidic ethanol solution is 2-3, and the volume fraction of ethanol is 40-55%.

5. The wear-resistant and anti-fouling UV coating according to claim 3, characterized in that: The fineness of corundum powder is 600-1000 mesh.

6. The wear-resistant and anti-fouling UV coating according to claim 1, characterized in that: The acrylate resin is selected from polyurethane acrylate resins.

7. The wear-resistant and anti-fouling UV coating according to claim 1, characterized in that: The active diluent is prepared by compounding dipropylene glycol diacrylate and trimethylolpropane triacrylate.

8. A method for preparing the wear-resistant and anti-fouling UV coating according to any one of claims 1 to 7, characterized in that: Specifically, the acrylic resin and the active diluent are mixed and diluted, and then the color paste, the base wetting agent, the leveling agent and the defoaming agent are added and mixed, and finally the modified anti-wear filler and the photoinitiator are added and ground and dispersed to obtain the UV coating.

Citation Information

Patent Citations

  • High-wear-resistance photocuring UV paint and production process thereof

    CN113322001A

  • Wear-resistant high-strength UV photocureable coating and preparation method thereof

    CN116694222A

  • Wear-resistant polyethylene gas pipe and preparation method thereof

    CN116731546A

  • Composite polytetrafluoroethylene gasket and preparation method thereof

    CN117227199A